2007
DOI: 10.1152/japplphysiol.01087.2006
|View full text |Cite
|
Sign up to set email alerts
|

Human lung density is not altered following normoxic and hypoxic moderate-intensity exercise: implications for transient edema

Abstract: The purpose of this study was to examine the effects of exercise on extravascular lung water as it may relate to pulmonary gas exchange. Ten male humans underwent measures of maximal oxygen uptake (Vo2 max) in two conditions: normoxia (N) and normobaric hypoxia of 15% O2 (H). Lung density was measured by quantified MRI before and 48.0 +/- 7.4 and 100.7 +/- 15.1 min following 60 min of cycling exercise in N (intensity = 61.6 +/- 9.5% Vo2 max) and 55.5 +/- 9.8 and 104.3 +/- 9.1 min following 60 min cycling exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Hodges et al (18) showed no changes in pulmonary density, which increases in the presence of extravascular lung water, following normoxic and hypoxic midintensive exercise. Conversely, Hopkins (19) demonstrated the presence of red cells, proteins, and leukotriene B4 in the bronchoalveolar lavage after brief maximal sea level exercise, suggesting the occurrence of transient increase in pulmonary blood-gas barrier permeability.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hodges et al (18) showed no changes in pulmonary density, which increases in the presence of extravascular lung water, following normoxic and hypoxic midintensive exercise. Conversely, Hopkins (19) demonstrated the presence of red cells, proteins, and leukotriene B4 in the bronchoalveolar lavage after brief maximal sea level exercise, suggesting the occurrence of transient increase in pulmonary blood-gas barrier permeability.…”
Section: Discussionmentioning
confidence: 96%
“…pulmonary edema EVEN IN HEALTHY SUBJECTS EXTREMELY demanding endurance exercise leads to functional and structural cardiac and pulmonary changes, along with local and systemic responses, reflecting oxidative, metabolic, hormonal, and thermal stress, besides immunomodulation and inflammatory reaction (4,30,32,40,41,46). Whether interstitial pulmonary edema occurs in athletes performing heavy sea level exercise is debated (2,6,12,18,19,27,28,44,56). Interstitial pulmonary edema has been documented in endurance athletes performing heavy sea level exercise, using imaging techniques such as chest X-ray, magnetic resonance, computed tomography, and scintigraphy (17,36,56).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While some controversy exists on the presence of exercise-induced pulmonary oedema [24][25][26], numerous case reports demonstrate the presence of pulmonary oedema after prolonged or high-intensity exercise [27], which, upon further evaluation, appears to be unrelated to abnormal cardiac function. Evidence for pulmonary oedema has been shown in competitive rowers [28], during exertion in dry cold environments and in cases of emotional stress and sexual intercourse [29], in addition to long distance runners and triathletes [30][31][32][33][34][35][36][37][38][39][40] and competitive cyclists [41,42].…”
Section: Exercise-induced Pulmonary Oedemamentioning
confidence: 99%
“…Given similar clinical and environmental parameters, exposure to intense prolonged exercise, exposure to high altitude, or development of heart failure can all lead to pulmonary edema in some, but not all, individuals (Caillaud et al, 1995; Hopkins et al, 1997). However, not all sojourners to high altitude, athletes, or patients with heart failure show evidence for pulmonary edema, suggesting a genetic component to one’s susceptibility to pulmonary edema formation (Guenette et al, 2007; Hodges et al, 2007; Hopkins et al, 1997; McKenzie et al, 2005). While lung fluid accumulation is primarily passive and follows Starling’s law, lung fluid clearance is an active process involving several pathways including activation of the amiloride sensitive epithelial sodium channel (ENaC).…”
Section: Introductionmentioning
confidence: 99%